(3Gdage GdUGFH ddCehQs - (3QhHQJ(B, (3L(B.(3HGQhs ((3YeGf(B:s (3OGQ GdcJGH GdMOjK(B,s, 2009)
(3Gdfeh GdEbJUGOj(B- (3GdSjGSI GdfbOjI hGdJehjdjI(B- (3GdSjGSI GdeGdjI ChGdEfaGbjI(B- (3GdVQjHI hSjGSGJ GbJUGOjI cdjI CNQi(B- (3bhI GdefWb Ch GdJYdjd GdEbJUGOjs
(3GdeQGLY U(B.147(3; cTGa GdehGVjY U(B.151s
Keywords: (3GdCShGbs; (3GdEbJUGOs; (3GdSjGSI GdfbOjIs